Resposta fisiológica, atividade de enzimas antioxidantes e conservação da banana prata tratada com etanol - França, Daiane Luckmann Balbinotti de (2016)
Ethanol has been studied as an inhibitor of ethylene biosynthesis, which can be of great benefit for the post-harvest conservation of fruits. However, studies have shown that some climacteric fruits, such as banana, did not respond to ethanol. The ability of the banana to absorb ethanol may be limited and interfere with its ethylene regulatory action. The objective of this work was to evaluate the effect of exposure time and ethanol dose on ethylene production, respiration, antioxidant enzymes and postharvest preservation of 'Prata' banana. A first sample of bananas was exposed to ethanol vapor (100 μL) for 10.0 hours. Another sample of bananas was exposed to 50, 100 and 150 μL of ethanol and then stored for 12 days. Respiratory rate, ethylene production, activities of the enzymes superoxide dismutase (SOD), catalase (CAT), ascorbate peroxidase (APX), phenylalanine ammoniumase (FAL) and polyphenoloxidase (PPO), physicochemical characteristics and degradation were evaluated. The respiration rate and ethylene production of ethanol treated bananas (71.13 mg CO2 kg-1 h-1 and 0.009 μg C2H4 kg-1 h-1, respectively) were lower than the control fruits (101.58 mg kg -1 h -1 and 0.014 μg kg -1 h -1, respectively), but this occurred only with 4 hours of exposure to ethanol, during which time there was a peak of ethanol uptake in the fruit. Ethanol caused higher SOD and CAT activity and less APX activity of banana bark only in the first two hours of exposure, but this was not related to ethylene production or respiratory rate. Ethanol influenced changes in PPO and FAL activities after the peak of its maximum absorption by the fruit (4 hours). During storage, ethanol caused a decrease in the ethylene production of the fruits, but there was no effect of the doses. Ethanol did not influence the respiratory rate, sugar conversion, texture and loss of fresh banana mass during storage. This study showed that ethanol has an effect on the metabolism of ethylene, but that this has no reflection on some quality parameters of 'Prata' banana. On the other hand, ethanol was able to delay the degradation of the fruit, and this is commercially advantageous.